Oropharyngeal Probiotic ENT-K12 as an Effective Dietary Intervention for Children With Recurrent Respiratory Tract Infections During Cold Season - Guo, Hongyan; Xiang, Xiaochen; Lin, Xuan; Wang, Qiang; Qin, Si; Lu, Xinyan; Xu, Jiawei; Fang, Ying; Liu, Yang; Cui, Jing; Li, Zhi (Frontiers in Nutrition, 2022)
Recurrent respiratory tract infections (RRTi) cause a high burden of disease and lead to negative impact on quality of life, frequent school/work absenteeism, and doctor visits, which remain a great challenge to pediatricians because RRTi can increase the risk of various complications including antibiotic overuse and resistance, which is one of the biggest threats to global health, and there is no confirmed effective treatment. In this study, we aimed to assess the clinical efficacy and safety of oropharyngeal probiotic ENT-K12 as a dietary intervention or a complementary treatment along with standard medical treatment during acute respiratory infections among children with RRTi during cold season. The results of this study show that when comparing to practicing of standard medical treatment only, the complementary intake of oropharyngeal probiotic ENT-K12 can effectively reduce episodes of both acute and RRTi in school children, shorten the course of respiratory symptoms onset, reduce the use of antibiotics and antiviral drugs, and reduce the absence days from both children's school and parents' work. Using oropharyngeal probiotics as a complementary dietary intervention to stabilize oropharyngeal microflora, specifically inhibiting respiratory pathogens and enhancing host immunity, could possibly be a promising approach to reduce RRTi burden and combating antibiotic resistance in long term, more clinical studies will be needed to further confirm the clinical practicing guide to ensure its clinical benefit. Methods A total of 100 susceptible children with RRTi aged 3–10 years, living in Wuhan, China, were selected. They were randomized to the probiotic group and control group at the beginning of the trial during the cold season. Fifty children in the probiotic group took oropharyngeal probiotic ENT-K12 for 30 days, along with standard medical treatment when there was an onset of respiratory symptoms and medical treatment was needed, and fifty children in the control group did not take oropharyngeal probiotics but only had standard medical treatment when there was an onset of respiratory symptoms and medical treatment was needed. Patients were followed up for 30 days during the cold season. The primary objective of this study is to assess the complementary dietary interventional efficacy of oropharyngeal probiotic ENT-K12 on episodes of respiratory tract infections during the cold season, and the secondary objective is to assess the interventional efficacy of oropharyngeal probiotic on days of respiratory symptoms onset, using antiviral drugs, antibiotics, and antipyretics, days of children absent from school, and days of parents absent from work, as well as to confirm tolerability and safety judged by adverse event reporting. Results There were 47 children, 22 male and 25 female children, with an average age of 5.71 years (SD = 1.99) in the probiotic group finishing the study, and 50 children, 32 male and 18 female children, in the control group with an average age of 6.12 years (SD = 1.98) finishing the study. During the 30-day period of oropharyngeal probiotic intake, children in the probiotic group totally had 7 episodes of upper respiratory tract infections, while children in the control group totally had 17 episodes of upper respiratory tract infections, indicating that the incidence of upper respiratory tract infection in the probiotic group (14.89%) was significantly lower than that in the control group (34.00%) during the intervention period. The days of using antibiotics and antiviral drugs in the probiotic group were significantly lower than that in the control group, and the course of respiratory symptoms onset was shorter and more moderate in the probiotic group than that in the control group; in addition, compared with the control group, both the days of children absent from school and parents' absence from work in the probiotic group were significantly lower. Children treated with oropharyngeal probiotic ENT-K12 had excellent tolerability with no side effects reported, hence confirmed safety of applying oropharyngeal probiotic ENT-K12 as a prophylactic use or an effective dietary intervention along with standard medication during respiratory infections onset. Conclusion Intake of oropharyngeal probiotic ENT-K12 as a dietary intervention can effectively reduce episodes of upper respiratory tract infections in school children with RRTi during high peak season, reduce the days of using antibiotics and antiviral drugs, and reduce children's sick leave days, parents' absence days from work, and shorten the course of respiratory infections; the safety of oropharyngeal probiotic ENT-K12 has been confirmed with no side effects reported, excellent tolerability, and easy acceptance. Notably, this study opens up a new research idea in the field of microbe promoting human health by supplying direct proof to support its efficiency and safety.